2019
DOI: 10.1002/app.47826
|View full text |Cite
|
Sign up to set email alerts
|

Tailored interphase and thermal interface resistance of self‐assembled thermally reduced graphene oxide–polyamide hybrid/epoxy composites with enhanced thermal conductivity

Abstract: Thermally reduced graphene oxide–polyamide (TrGO‐PA) hybrids were fabricated by self‐assembly between TrGO nanosheets and PA microparticles, and the dispersibility, interphase extension, and thermal conduction mechanism of TrGO‐PA/epoxy (EP) composites were investigated. Most of the oxygen‐containing functional groups of TrGO were removed, and a conjugated structure of graphene was recovered. TrGO was distributed evenly on the PA surface via electrostatic adsorption between TrGO and PA, which resulted in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Hence, it can be concluded that smaller NPs contribute to the construction of a filler network, which implies a higher TC. However, this does not seem to be consistent with many experimental results [56][57][58] in which larger fillers more easily form an overlapping network and lead to a higher thermal conductivity of polymer composites. A conductive network formed by larger fillers could result in more heat being transferred by the high thermal conductivity fillers themselves.…”
Section: Filler Size and Volume Fractioncontrasting
confidence: 80%
“…Hence, it can be concluded that smaller NPs contribute to the construction of a filler network, which implies a higher TC. However, this does not seem to be consistent with many experimental results [56][57][58] in which larger fillers more easily form an overlapping network and lead to a higher thermal conductivity of polymer composites. A conductive network formed by larger fillers could result in more heat being transferred by the high thermal conductivity fillers themselves.…”
Section: Filler Size and Volume Fractioncontrasting
confidence: 80%
“…The comparison of thermal conductivity of epoxy composites with different fillers for the current study and previous works is shown in Table 4. [31,35,36,[41][42][43][44][45][46][47] The composite with 12 wt % (TC = 0.590 W/mK) is useful for electronic circuit encapsulation as sufficient thermal management is achieved, one such electronic circuit encapsulation is shown in Figure 9.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…[59,60] The corrosion resistance further increased for DHMMPE/GA composite (1%), that is, 1.5165 × 10 −4 mm/year, which is due to hydrophobic nature, good mechanical properties, and large surface area of graphene [61] and good impermeability of graphene. [55] Further increase of GA [36] Exfoliated graphite 8 wt% 0.500 [41] Reduced graphene oxide 0.5 wt% 0.184 [42] CNT 1.5 wt% 0.183 [43] MWCNT 0.5 wt% 0.247 [44] Silicon carbide nanowires 3 wt% 0.449 [35] Al 2 O 3 67 wt% 0.57 [45] BN 35.5 wt % 0.59 [45] AlN 57 vol% 1.5 [46] SiO 2 5 wt% 0.177 [47] T-ZnO 50 wt% 4.38 [31] Abbreviations: AlN, aluminum nitride; BN, boron nitride; T-ZnO, tetrapodshaped ZnO. concentration (3-5%) in the composite did not increase the corrosion resistance but decreased.…”
Section: Anticorrosion Propertiesmentioning
confidence: 99%
“…However, due to the small size effect, the fillers tend to agglomerate in the polymer, which is not conducive to the formation of the ordered heat conductive framework. [ 11–13 ] Therefore, current research on thermally conductive composites has mainly focused on uniformly dispersing small‐sized fillers and regulating the arrangement of fillers. [ 6,14–17 ] By constructing heat conduction paths through three‐dimensional (3D) network, the high thermal conductivity of the material can be obtained.…”
Section: Introductionmentioning
confidence: 99%